Never sniff a gift fish [large type] - McManus, Patrick F. (G.K. Hall, 1984)
McManus will teach you the wisdom that is usually shared only in the close ranks of modern-day hunters and gatherers. Whether he's poking fun at fly fishing or taking on some other sportsman's icon, he is sure to have you laughing out loud.